Adjacent Level Degeneration: Bryan Total Disc Arthroplasty Versus Anterior Cervical Discectomy and Fusion. Issue 2 (March 2018) - Miller, Justin; Sasso, Rick; Anderson, Paul; Riew, K. Daniel; McPhilamy, Austin; Gianaris, Thomas
Abstract : Study Design: Prospective randomized, 2-center, clinical trial. Objective: To prospectively compare adjacent level degeneration between the Bryan Cervical Disc Prosthesis and anterior cervical discectomy and fusion (ACDF), and assess the reliability of our measurements utilizing a method not previously described. Summary of Background Data: ACDF is a reliable and proven procedure for the treatment of radiculopathy and/or myelopathy. Despite a successful track record several limitations including adjacent segment degeneration/disease, loss of viscoelastic disc properties, perioperative immobilization, graft site morbidity, pseudarthrosis, and plating complications have been identified. An original driving force and theoretical basis for total disc arthroplasty was prevention of adjacent level degeneration. Materials and Methods: Seventy-nine patients were enrolled and followed prospectively at 2 centers in a multicenter, Food and Drug Administration Investigational Device Exemption trial for the Bryan Cervical Disc arthroplasty. Neutral lateral radiographs were obtained preoperatively and postoperatively, and at 1-, 2-, 4-, and out to 7-year follow-up after surgery. The cephalad, adjacent level above the blinded procedure level was analyzed for all patients and time points by measuring the anteroposterior distance and the vertical disc height. A ratio was created using disc height/anteroposterior distance. Results: Seventy patients (Bryan Cervical Disc N=34 and ACDF N=36) met inclusion criteria. Both fusion and arthroplasty groups showed a significant ( P =0.001) decrease in disc height over time, indicative of adjacent level degeneration. Overall change in disc height between groups was not significantly different. Using our measurement technique, the overall interreviewer reliability was good [intrareviewer correlation coefficients (95% confidence interval)=0.77 (0.55–0.85)] and intrareviewer reliability was excellent [0.93 (0.91–0.94) and 0.85 (0.81–0.87)]. Conclusions: Adjacent level degeneration occurs in a similar manner in both the ACDF and total disc arthroplasty group. Our measurement technique is reliable and to the best of our knowledge not previously reported in the literature.